Video Animasi sebagai Media Edukasi Pencegahan Anemia pada Remaja Putri - Silva agustini Hanifah; Ayu Laili; Agus Riyanto; Novie Mauliku; Suhat Suhat (Universitas Faletehan, 2025)
Adolescent girls are a vulnerable group to anemia, which can increase the risk of complications during pregnancy and childbirth. This study aimed to evaluate the effects of health promotion through animated video on adolescent girls’ knowledge, attitudes, and adherence to iron supplementation in preventing anemia. A quasi-experimental design with a non-equivalent control group was employed, involving all seventh-grade students of SMP Negeri 1 Rancaekek, Bandung Regency, West Java who met the inclusion criteria (n = 152). The group allocation was conducted using purposive sampling. Data analysis included frequency distribution, T-test and Wilcoxon test for bivariate analysis, and logistic regression for multivariate analysis. The results showed a significant improvement in the intervention group: knowledge (p ≤ 0.001), attitudes (p = 0.001), and adherence to iron supplementation (p ≤ 0.001). The novelty of this study lies in the use of interactive animated video, which not only improves knowledge but also enhances attitudes and adherence among adolescent girls. The findings suggest that animated videos are effective as an educational medium for anemia prevention in adolescent girls and recommend routine monitoring as well as support from health workers to promote synchronized consumption of iron tablets at school.